Esters of omega-amino acids as flexible penetration enhancers - Hrabálek, A; Dolezal, P; Roman, M; Machácek, M; Sklubalová, Z (Die Pharmazie, 1994)
Series of esters of 6-aminohexanoic acid, 7-aminoheptanoic acid, and 8-aminooctanoic acid were synthesized as candidates for novel skin penetration enhancers. The permeation of theophylline expressed in the form of the enhancement factor (EF) was studied with human cadaver skin by a diffusion cell technique in the presence of the esters 1-17 in the water vehicle. The permeation in the presence of the 6-aminohexanoates 1-5 was also studied in the olive oil vehicle. Of the compounds tested, the most satisfactory enhancement in the water vehicle and oil vehicle were observed with octyl 6-aminohexanoate (EF = 45.5) and decyl 6-aminohexanoate (EF = 19.5), respectively.
Keywords: aminokyseliny; pomocné látky; Structure-Activity Relationship; theofylin; Diffusion; vysokoúčinná kapalinová chromatografie; techniky in vitro; Excipients; magnetická rezonanční spektroskopie; difuze; Magnetic Resonance Spectroscopy; Theophylline; Chromatography, High Pressure Liquid; vztahy mezi strukturou a aktivitou; lidé; Humans; kožní absorpce; Skin Absorption; In Vitro Techniques; Amino Acids